“Quo Vadis Infotainment”? - Ahmadi, Dadi (Mediator, 2008)
According to Marshall McLuhan, the world has become a global village where modern communication media opened up unlimited interactions among people all over the world. Among other things, mass communication channel has rapidly developed, allowing greater mass of information transmissions to be spread for all members of society in no time. Unfortunately, the rapid development of mass media was not followed by better quality in terms of media content. Infotainments were everywhere, offering latest report concerning celebrity news in detail, and raising serious questions concerning ethics, privacy, public policy, and news quality today.